Pelaksanaan Pendidikan Kewirausahaan di Pendidikan Tinggi - Siswo Wiratno (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2012)
The aims of this study is to analyze the implementation of entrepreneurship education in higher education, in relation to the competencies of graduates as expected by labour market and other supporting competencies. Problems related to entrepreneurship education, among others include: 1) preparation and implementation of entrepreneurship education program as well as the role of a new unit responsible to manage the program is not optimal; 2) provision of facilities and infrastructure for entrepreneurial implementation is still limited (means and infrastructure, partners, funding and competent lecturers in the subject of entrepreneurial skills). The assessment results showed that: 1) implementation of entrepreneurship education in various higher education institutios is not yet optimal, partly due to the failure of entrepreneurialmanagement unit in optimizing its role and function; 2) competency of higher education graduates has not fully meet the expectations of the labour market, as they are expected to have academic competency, thinking skills, management skills and communication skills. In addition, graduates are not equipped with adequate live skills, ability to adapt and socialize with the working environment and life-long education.ABSTRAK Tujuan kajian ini dimaksudkan untuk menganalisis pelaksanaan pendidikan kewirausahaan di perguruan tinggi, kaitannya dengan kompetensi lulusan yang diharapkan oleh dunia kerja dan kompetensi pendukung lainnya. Permasalahan yang berkaitan dengan pendidikan kewirausahaan antara lain: 1) persiapan dan pelaksanaan program kewirausahaan dan peran unit baru yang berfungsi dan bertugas sebagai pengelola program kewirausahaan belum optimal; 2) penyediaan sarana dan prasarana penyelenggaraan kewirausahaan yang masih terbatas (sarana dan prasarana, mitra kerja, dana,dan tenaga dosen yang berkompetensi dalam memberi bekal keterampilan kewirausahaan Hasil kajian menunjukkan bahwa: 1) pelaksanaan pendidikan kewirausahaan di berbagai perguruan tinggi belum dilaksanakan secara optimal, antara lain disebabkan oleh belum optimalnya peran dan fungsi unit pengelola kewirausahaan; 2) kompetensi lulusan perguruan tinggi masih belum sepenuhnya memenuhi harapan dunia kerja, di mana diharapkan para lulusan perguruan tinggi memiliki kompetensi akademik, keterampilan berpikir, keterampilan manajemen dan keterampilan berkomunikasi. Di samping itu, lulusan belum cukup dibekali dengan keterampilan hidup (live skill), kemampuan beradaptasi dan bersosialisasi dengan lingkungan kerja serta belajar sepanjang hayat (lifelong education).